Protective Material Coatings for Preserving Cultural Heritage Monuments and Artwork - Langroudi, Amir Ershad (Bentham Science Publishers, 2022)
Long-standing artworks and monuments show the wisdom and cultural identity of an ancient society along with the educational, material and spiritual merits of the people of that time. However, many historical artifacts and cultural monuments have been eroded over time and are in danger of deterioration beyond repair. There is a need to protect and conserve these artifacts. Restoration and preservation requires a multidisciplinary understanding of the inherent properties of these works based on the type of material and sufficient information in the properties of protective and conservation mater.